The influence of socio-economic status on the fulfilment of Saint-Gallen recommendations for early-stage breast cancer - Trinidad Dierssen-Sotos; Inés Gómez-Acebo; Jéssica Alonso-Molero; Beatriz Pérez-Gómez; Marcela Guevara; Pilar Amiano; Gemma Castaño-Vinyals; Alba Marcos-Delgado; Mónica Mirones; Mireia Obón-Santacana; Guillermo Fernández-Tardón; Ana Molina-Barceló; et al. (Scientific Reports)
Abstract Socio-economic status (SES) is related to breast cancer diagnosis and prognosis. We study if SES is related to the adequacy of the treatment according to Saint Gallen consensus in Spanish women with incident breast cancer. Breast cancer cohort was assembled from incident cases from MCC-Spain and prospective followed-up afterwards. Participants were then classified according to the Saint-Gallen consensus in three categories (In Saint-Gallen, who received therapy accorded by Saint Gallen; Over Saint-Gallen, who received some additional therapy; or Under Saint-Gallen, who did not receive the complete therapy). Association between SES and Saint-Gallen fulfilment was analyzed using multinomial logistic regression, adjusting for clinicopathological and patient-related variables. 1115 patients in stages I and II were included. Women with university education were 58% more likely to receive over Saint-Gallen therapies (RRR = 1.68; 95%CI 0.84–3.33). In the simplified SES score, women with higher SES were over Saint-Gallen 52% more than those with lower SES (RRR = 1.52; 95%CI 0.88–2.64). Women with higher SES more often received over Saint-Gallen therapies. Further analyses are needed to understand the influence of these differences on the overall survival as well as its potential unwanted side effects.